2009
DOI: 10.1589/jpts.21.355
|View full text |Cite
|
Sign up to set email alerts
|

Does Instability during Standing Occur just after Transcutaneous Xenon Light Irradiation around the Stellate Ganglion?

Abstract: Abstract. [Purpose] This study investigated whether instability during standing occurs just after transcutaneous xenon light irradiation around the stellate ganglion.[Subjects] Thirty healthy volunteers were the subjects.[Methods] The subjects underwent two experimental sessions: 1) 10-minute xenon light irradiation around the bilateral stellate ganglions in a comfortable supine position (Xe-LISG); and 2) 10-minute rest in the same position as Xe-LISG (control). After Xe-LISG and the control, they stood up im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Nacitarhan et al indicated that SGB performed using therapeutic US exerts positive effects on the autonomic nervous system by altering HRV parameters, particularly by reducing the low to high frequency power ratio [42]. Similar results were reported by Yoshida et al [34]. In this study, we identified significant sympatholytic effects immediately after noninvasive SGB, regardless of the electrophysical modality used.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Nacitarhan et al indicated that SGB performed using therapeutic US exerts positive effects on the autonomic nervous system by altering HRV parameters, particularly by reducing the low to high frequency power ratio [42]. Similar results were reported by Yoshida et al [34]. In this study, we identified significant sympatholytic effects immediately after noninvasive SGB, regardless of the electrophysical modality used.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, numerous noninvasive approaches for SGB employing physical agent modalities (PAMs) have been developed as alternatives to the conventional invasive anesthetic technique, including therapeutic ultrasound (US), transcutaneous electrical nerve stimulation (TENS), light irradiation using low-level laser therapy (LLLT), and xenon light and linearly polarized near-infrared (LPNIR) light irradiation near or over the stellate ganglion region. In addition, noninvasive SGB can be safely and conveniently performed in clinical practice, particularly in patients declining injections, having a high bleeding tendency, undergoing anticoagulant therapy, or having contraindications for nerve blockade, such as those with hemophilia [3034]. In patients with neuropathic pain syndromes, the effects of SGB performed using light irradiation were similar to those of conventional intensive SGB, including improved blood flow through vasodilation and reduced pain by direct blockade of the afferent nociceptive signals traveling through sympathetic pathways [31, 33, 35–38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown the effects of stellate ganglion irradiation (SGI) with various types of light in patients with diverse diseases who responded to SGB 14 , 16 ) . SGI, with its lack of serious side effects, may be a promising treatment method that could replace SGB 13 , 15 ) .…”
Section: Introductionmentioning
confidence: 99%